2023
DOI: 10.3390/ijms24097908
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR-4669 Enhances Tumor Aggressiveness and Generates an Immunosuppressive Tumor Microenvironment in Hepatocellular Carcinoma: Its Clinical Value as a Predictive Biomarker

Abstract: Accumulating evidence suggests the involvement of tumor-derived exosomes in the development and recurrence of hepatocellular carcinoma (HCC). We previously identified miR-4669 as a highly expressed microRNA in circulating exosomes obtained from patients with post-transplant HCC recurrence. This study aimed to explore how overexpression of miR-4669 affects HCC development and recurrence. The impact of miR-4669 overexpression in Hep3B cells on tumor cell behavior and the tumor microenvironment was evaluated in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…This interaction has been found to cause the spread of HCC and is associated with a worse overall survival rate in HCC patients [ 40 ]. The upregulation of miR-4669 resulted in the increased migratory capacity of HCC cells and conferred resistance to sorafenib treatment, accompanied by an upregulation of sirtuin 1 [ 41 ]. Zhang et al [ 42 ] observed that exosomal circ_0046600 could facilitate the advancement of HCC by sequestering miR-1258 and subsequently upregulating SERBP1.…”
Section: Exosomes and Hccmentioning
confidence: 99%
“…This interaction has been found to cause the spread of HCC and is associated with a worse overall survival rate in HCC patients [ 40 ]. The upregulation of miR-4669 resulted in the increased migratory capacity of HCC cells and conferred resistance to sorafenib treatment, accompanied by an upregulation of sirtuin 1 [ 41 ]. Zhang et al [ 42 ] observed that exosomal circ_0046600 could facilitate the advancement of HCC by sequestering miR-1258 and subsequently upregulating SERBP1.…”
Section: Exosomes and Hccmentioning
confidence: 99%
“…Another study showed that higher levels of miR-320d in serum EVs were linked to better recovery in HCC patients after surgery ( 92 ). Moreover, the expression of plasma exosomal miR-4669 could predict HCC recurrence after liver transplantation with specificity and sensitivity at around 75% ( 93 ). The expression of exosomal miR-122 was found to be significantly reduced post transarterial chemoembolization (TACE), and the ratio of serum exosomal miR-122 post TACE as compared to pre-TACE was positively correlated with prolonged disease-specific survival, indicating its potential clinical utility ( 94 ).…”
Section: Clinical Implications and Therapeutic Opportunitiesmentioning
confidence: 99%
“…Therefore, exosomal circRNA-SORE plays a crucial role in the maintenance and transmission of sorafenib resistance in HCC [15] . In addition, exosomal miR-494-3p, upregulated by the oncoprotein Golgi phosphoprotein 3 (GOLPH3), has been found to be transferred to recipient human umbilical vein endothelial cells (HUVECs) and HCC cells, suppressing PTEN protein expression by directly targeting the 3' UTR of PTEN mRNA, and subsequently promoting angiogenesis and enhancing sorafenib resistance [25] .…”
Section: Exosomes Induce Molecular Targeted Therapy Resistance In Hccmentioning
confidence: 99%